Refractive index measurement using single fiber reflectance spectroscopy. Issue 7 (3rd April 2019) - Zhang, Xu U.; Faber, Dirk J.; Post, Anouk L.; van Leeuwen, Ton G.; Sterenborg, Henricus J. C. M.
Abstract : A method using single fiber reflectance spectroscopy to measure the refractive indices of transparent and turbid media over a broad wavelength range is presented and tested. For transparent liquid samples, the accuracy is within 0.2%, and the accuracy increases with increasing wavelength. For liquid turbid media, the accuracy is within 0.3% and increases with decreasing wavelength. For solid turbid samples, such as human skin, the accuracy critically depends on the optical contact between the fiber and sample surface. It is demonstrated that this technique has the potential to measure refractive indices of biological tissue in vivo. Abstract : The refractive index is of great importance for applications in both engineering and research. However, the desired information is not always available or only available at certain wavelengths. Frustrating? Now we have a solution for you: we present a method based on the Fresnel reflection to measure the refractive index spectrum of transparent and turbid media using single fiber reflectance spectroscopy with excellent accuracy.